Stated choices and simulated experiences: Differences in the value of travel time and reliability. (July 2021) - Fayyaz, Muhammad; Bliemer, Michiel C.J.; Beck, Matthew J.; Hess, Stephane; van Lint, J.W.C.
Highlights: Novel incentive compatible driving simulator experiment to determine value of travel time reliability. Within‐respondent design to compare route choice behaviour with and without time and cost consequences. Compared to a traditional stated choice survey,  differences in route choices are observed mainly due to cost consequences. Completing a driving simulator experiment first makes route choices in a follow‐up stated choice survey more consistent. Abstract: Surveys with stated choice experiments (SCE) are widely used to derive values of time and reliability for transport project appraisal purposes. However, such methods ask respondents to make hypothetical choices, which in turn could create a bias between choices made in the experiment compared to those in an environment where the choices have consequence. In this paper, borrowing principles of experimental economics, we introduce an incentive compatible driving simulator experiment, where participants are required to experience the travel time of their chosen route and actually pay any toll costs associated with the choice of a tolled road. In a first for the literature, we use a within respondent design to compare both the value of travel time savings (VTT) and value of travel time reliability (VOR) across a typical SCE and an environment with simulated consequence. Given the importance of VTT and VOR to transport decision making and the difficulty in estimating VOR using revealed preference data, our results are noteworthy and emphasise that more research on this topic is imperative. We provide suggestions on how the results herein may be used in future studies, to potentially reduce hypothetical bias that may be exhibited in SCE.